Ultrafast Photoluminescence from the Core and the Shell in CdSe/CdS Dot‐in‐Rod Heterostructures. Issue 5 (4th November 2015) - Diroll, Benjamin T.; Turk, Michael E.; Gogotsi, Natalie; Murray, Christopher B.; Kikkawa, James M.
Abstract: With an ultrafast time‐resolved photoluminescence system utilizing a Kerr gate, the time‐resolved photoluminescence of core and shell constituents within CdSe/CdS dot‐in‐rod heterostructures is studied as a function of heterostructure size. Measurements performed at low excitation fluence generating, on average, less than one exciton per nanorod, reveal photoluminescence from direct recombination of carriers in the CdS heterostructure rod with lifetime generally increasing from 0.4 ps to 1.3 ps as the rod length increases. Decay of the CdS rod photoluminescence is accompanied by an increase in emission from the CdSe core on comparable time scales, also trending towards larger values as the rod length increases. The observed kinetics can be explained without invoking a non‐radiative trapping mechanism. We also present alloying as a mechanism for enhancing electron confinement and reducing fluorescence lifetime at nanosecond time scales. Abstract : Going dotty : Ultrafast photoluminescence of CdSe/CdS dot‐in‐rod heterostructures is detected from both the dot and the rod. Due to hole transfer, photoluminescnence from the rod decays as dot photoluminescence grows.